A Combined Recombinant Retroviral-Based Therapy for Colon Cancer in the Murine Model Using Anti-Tumorigenic and Anti-Angiogenic Agents - Nik Abd. Rahman, Nik Mohd. Afizan (2011)
Anti-tumorigenic gene therapy offers many benefits over than conventional therapy i.e., chemotherapy or radiotherapy including less toxic side effects, rapid delivery and more sensitive compared to target-based drugs. Anti-tumorigenic agents alone were not proven to be effective in promoting the delay or regression of tumor mass in vivo due to low therapeutic gene transfer efficiency and the formation of new blood vessels in tumors. In addition, the blood vessels are one of the major factors that reduce the effectiveness of anti-tumorigenic agents. Consequently, a new therapeutic approach that combined both anti-tumorigenic and anti-angiogenic agents was established and proven to provide superior and beneficial synergistic effect. In the present study, a complete open reading frame (ORF) encoding endostatin protein was RNA extracted from a Balb/c mice liver tissue and transcribed into cDNA. The gene was then cloned into TOPO vector prior to a retroviral vector, pMSCVneo. Upon cloning and sequencing of the full length of the gene, it was revealed that the complete ORF contained 550 nucleotides, by which the size similar to that of established endostatin. While, anti-tumorigenic gene; VP3 was obtained from previous study (generous gift from Professor Mohd Azmi Mohd Lila) and verified by PCR approaches. The PCR amplification and restriction endonuclease analysis showed that the gene product was convenient and similar to the expected size. The gene obtained was also 98% homology to that the references strain, Cux-1 by DNA sequencing analysis. Both recombinant constructs were transfected into PT67 cells and the transiently produced virus used to treat Balb/c mice with established colon tumors. The method of treatments was given in either as single modality or combined treatment with standardized of tumor size in each mice group. Here, we also revealed a viral delivery vehicle named 'retroviral vector’ to deliver the both anti-tumorigenic and anti-angiogenic agents into the tumor mass to achieve the effects of apoptosis. Furthermore, the retroviral-mediated gene therapies also showed no signs of adverse effect. Based on PCR approaches, the recombinant retrovirus particles were disseminated into the bloodstream and finally presented in various tissues but only expressed their therapeutic genes in tumors. As a result, the risk of undesirable characteristics of cancer gene therapy could be avoided in non-target tissues. The differential activities of VP3 and endostatin were investigated by the use of the immunohistochemistry analysis such as PCNA and vWF. The apoptosis activities upon expression of VP3 and endostatin were further studied by quantifying and identifying biochemical changes and number of affected cells due to apoptosis. Upon TUNEL and DNA fragmentation assays, typical apoptotic patterns were observed, to include formation of apoptotic bodies and visible DNA ladders, as early as 48 hours after treatments. Since necrotic cells could be stained positively by TUNEL, a flow cytometry assay was developed for identifying and quantifying dead or dying cells in mode of cell death. The apoptosis percentage including early and late apoptotic quadrants showed that the combined tumor treatment was higher than VP3 and endostatin only. The effect of VP3 and endostatin protein expression in tumor and vital organ tissues were also confirmed upon examination by inverted microscopy analysis with H&E-stained sections. In addition, upon electron microscopic examination, typical morphological apoptotic features were observed including intact membranes and organelles, cell blebbing as well as condensed nuclear membranes in single- and combined-treated tumors not in other vital organ tissues. Interestingly, based on these constructive findings the combined treatment noted better responses in tumor bearing mice rather than single treatments. In conclusion, this study showed that the combined approach was more promising, effective and good governance on delay tumor growth and inducing apoptosis than introducing VP3 or endostatin alone. The combination treatment also offers potential benefits in control of tumorigenesis, and thus deserves further research as a preferred approach in cancer gene therapy.